2013
DOI: 10.12988/es.2013.3109
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the brain: the impact of natural versus urban scenes using novel EEG methods in an experimental setting

Abstract: BackgroundResearchers in environmental psychology have consistently shown the restorative potential of natural -over urban -settings using video/photographic experiments in laboratory settings applying subjectively rated scales. But few studies have employed objective indicators of emotional response. This study investigates the use of electroencephalography (EEG) as a method to understand how the brain engages with natural versus (vs) urban settings -in tandem with subjective preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 11 publications
7
87
2
2
Order By: Relevance
“…Studies have shown that students can represent the public on research involving visual stimuli [38]. The limited number of interviewed is in line with similar studies in the topic of VR application and EEG analysis [39,40]. The recruitment occurred within the Territorial, Urban and Environmental Planning course of the University of Florence and the sample included millennials that did not attend forestry science classes, in order not to affect preferences and perceptions of forests.…”
Section: Sample Recruitment and Interviewsmentioning
confidence: 54%
“…Studies have shown that students can represent the public on research involving visual stimuli [38]. The limited number of interviewed is in line with similar studies in the topic of VR application and EEG analysis [39,40]. The recruitment occurred within the Territorial, Urban and Environmental Planning course of the University of Florence and the sample included millennials that did not attend forestry science classes, in order not to affect preferences and perceptions of forests.…”
Section: Sample Recruitment and Interviewsmentioning
confidence: 54%
“…Laboratory data using a mobile electroencephalography (EEG) headset (Emotiv EPOC+; validated for both laboratory and outdoor settings [17,18]) showed outputs that corresponded with self-reported measures on attractiveness, willingness to visit, valence and arousal of static images of landscapes or urban scenes [19]. This study used data from the Affectiv Suite, Emotiv proprietary software, which analyzes EEG from distinct brain activity patterns and allocates a label defining an emotional parameter ('frustration', 'excitement', 'engagement', 'meditation', 'long term excitement').…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism has been supported by previous work finding links between green space and biomarkers of stress. Two studies in Scotland found that viewing green areas, either as images or by walking through them, increased levels of meditation and decreased levels of arousal 45 46. Two other studies, both conducted in the UK, found that higher levels of green space were associated with decreased stress, measured by mean levels and diurnal patterns of cortisol, as well as self-reported stress, in residents of socioeconomically deprived neighbourhoods 47 48…”
Section: Discussionmentioning
confidence: 99%